Изучение возможности эндогенного синтеза формальдегида из креатина у людей в зависимости от их инфицированности Хеликобактером пилори - Дмитренко, Н.П.; Шандренко, C. Г.; Кишко, Т.О. (Видавничий дім "Академперіодика" НАН України, 2007)
We have performed the clinical research involving the analysis of mouth cavity air probes for the content of ammonium and formaldehyde after oral consumption of carbamide and creatine, accordingly. It has been found that 25 percents of volunteers with positive urease test, that indicates the Helicobacter pylori infection, had increased level of formaldehyde in air probes. Analysis of the reciprocal relations of ammonium and formaldehyde generation rates shows the possibility to form hexamethylentetramine (urotropine) in human stomach with the Helicobacter pylori infection.